2003
DOI: 10.1590/s0066-782x2003000100005
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of in-hospital mortality and of severe perioperative complications in myocardial revascularization surgery

Abstract: At the beginning of the 20 th century, cardiovascular diseases accounted for less than 10% of the deaths in the world. At the end of that century, that group of diseases accounted for approximately half of the deaths in the developed countries and 25% of the deaths in developing countries. In 2020, cardiovascular diseases are estimated to ount for 25 million deaths per year, and ischemic heart diseases will surpass infectious diseases as the first cause of death in the world 1 .In Brazil, cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
1
6
0
5
Order By: Relevance
“…This variable was also identified as a prognostic marker in a study of post-operative morbidity after myocardial revascularization in Brazil. The odds ratio for patients operated under care through the Public Health System was 3.89; for diabetes mellitus 2.25; for renal failure 6.04; and for cardiogenic shock 10.58 [19]. Thus, care under the Public Health System may be a marker of a clinical and socioeconomic conditions associated with less favorable outcomes either in heart failure or post-operative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This variable was also identified as a prognostic marker in a study of post-operative morbidity after myocardial revascularization in Brazil. The odds ratio for patients operated under care through the Public Health System was 3.89; for diabetes mellitus 2.25; for renal failure 6.04; and for cardiogenic shock 10.58 [19]. Thus, care under the Public Health System may be a marker of a clinical and socioeconomic conditions associated with less favorable outcomes either in heart failure or post-operative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The results are worse among patients whose hospitalization was financed by the SUS. 50,51 This disparity can be attributed both to the lower socioeconomic conditions of SUS patients and the greater difficulty in timely access to health facilities, as in the case of myocardial infarction, and to lesser use of evidence-based therapies, as well. 49 A recently published cluster-randomized clinical trial showed that quality improvements tools for acute coronary syndrome implemented in Brazilian public hospitals resulted in significant improvement of in-hospital cardiovascular event rates and 30-day all-cause mortality.…”
Section: Current and Novel Strategies For Disease Prevention And Treamentioning
confidence: 99%
“…Na população, em cada três indivíduos, um é portador de doença crônica 2 . No Brasil, as DACs são responsáveis por 33% dos óbitos com causas conhecidas, tendo sido a primeira causa de hospitalização no setor público para indivíduos com idade entre 40 e 59 anos 3 e para os com 60 ou mais anos 4 . Diversos fatores contribuem para a quantidade e qualidade de anos que se vive, incluindo fatores genéticos, ambientais e comportamentais, sendo alguns modificáveis e outros não.…”
Section: R Bras CI Saúde 18(sup4):51-58 2014unclassified